The Influence of Business Management on The Optimization of Fixed Asset Management (Case Study at PT KAI (Persero) Regional Division I North Sumatera) - Vina Estetica Situmorang; Harris Pinagaran Nst; Desri Wiana (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
Asset management is one of the keys to successful management of the country's economy. Optimal asset management by prioritizing maximum asset performance on the one hand is expected to be able to increase the trust in state financial management from companies. However, there is still administrative disorder in the management of fixed assets in several BUMN companies. The aim of this study was to determine the effect of Asset Inventory, Legal Audit, Asset Appraisal, Asset Control and Monitoring on the Optimization of Fixed Asset Management (land and buildings) at PT KAI (Persero) Regional Division I North Sumatra. The population of this study are active (permanent) employees at PT KAI (Persero) Regional Division I North Sumatra. Selection of the sample using the Non-probability sampling method. The sample used in this study was 94 respondents. The analysis tool used is multiple linear regression test using a statistical tool in the form of SPSS for windows. The results of hypothesis testing indicate that Asset Inventory, Legal Audit have a positive and significant effect on the Optimization of Fixed Asset Management at PT KAI (Persero) Regional Division I North Sumatra. Meanwhile, Asset Valuation, Control and Supervision of Assets have a positive and not yet significant effect on the Optimization of Fixed Asset Management at PT KAI (Persero) Regional Division I North Sumatra. Simultaneous tests show the results that the variables Asset Inventory, Legal Audit, Asset Appraisal, Asset Control and Supervision together influence the Optimization of Fixed Asset Management.